Effect of Environmental Factors on Milk Production Traits and Energy-Corrected Milk Yield in Karan Fries Cattle - Upadhyay, Arpan; Chakravarty, A. K.; Dash, Soumya; Shivahre, Pushp Raj; Gonge, Dimpee Singh (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted to analyze milk production traits and energy-corrected milk yield using 11569 first lactation milk production records of 1393 Karan Fries cows, calved between 1989 and 2014. The overall least-squares means of first lactation milk production traits viz. fat %, solids-not-fat (SNF)%, total solids (TS) %, 305 days milk yield (305dMY), fat yield (FY), SNF yield (SNFY), TS yield (TSY), the energy value of milk (E) and energy corrected milk yield (ECMY) were 4.20±0.01, 8.77±0.01, 12.97±0.01, 3142.58±24.45 kg, 132.37±1.03 kg, 275.41±2.14 kg, 407.78±3.16 kg, 750.57±0.60 Kcal kg-1 and 3229.88±24.37 kg, respectively. All the yield traits including ECMY were found higher in the autumn season and lower in the summer season. The ECMY was highest for the cows calved after 37 months of age and lowest for the cows calved at an early age. The milk fat % had a very high and positive correlation with TS %, indicating that cows with higher fat content tend to have higher TS content in milk, whereas, SNF % had a very low and negative correlation with all the milk production traits except TS % and energy value of milk. The correlation between 305dMY and ECMY was also found to be very high and positive, indicating that the current breeding policy based on milk yield of cows for genetic improvement of dairy breeds is in the right direction as it tends to increase milk yield along with energy-corrected milk yield of animals.